Lymphomyosot is a Biological Regulative Approach to the Therapy of Infantile Diseases - S.V. Popovich (Zaslavsky O.Yu., 2015)
Child's body is very sensitive to the effects of various contagiums, toxins, chemical agents as well as psychological stress [1]. Enhanced antigenous load on the child's body under the modern ecological, economic and social conditions changed the course of lots of diseases. Firstly nowadays the negative moments in the child's health are high rate of combined pathologies of organs and systems, increased occurrence of firstly diagnosed allergic states, distribution of diseases associated with acute or chronic endotoxemia [2]. That is why it is of great importance to direct therapeutic and preventive efforts of pediatricians to minimize the effect of negative endogenous factors on a child's body [1]. This publication presents the review of clinical works demonstrating the experience of clinical application of complex bioregulative agent Lymphomyosot produced by German company Biologische Heilmittel Heel GmbH in common infantile diseases [3-5]. Lymphomyosot is a basic drainage complex bioregulative agent improving lymph outflow from tissues and organs, having detoxication and anti-inflammatory effects that could reduce inflammation till its full disappearance. Lymphomyosot has a favorable safety profile and a good tolerance [1, 2, 6-15]. Permitted for use from the birth.